Screening Active Compounds from Garcinia Species Native to China Reveals Novel Compounds Targeting the STAT/JAK Signaling Pathway. (18th May 2015) - Xu, Linfeng; Lao, Yuanzhi; Zhao, Yanhui; Qin, Jian; Fu, Wenwei; Zhang, Yingjia; Xu, Hongxi
Abstract : Natural compounds from medicinal plants are important resources for drug development. In a panel of human tumor cells, we screened a library of the natural products from Garcinia species which have anticancer potential to identify new potential therapeutic leads and discovered that caged xanthones were highly effective at suppressing multiple cancer cell lines. Their anticancer activities mainly depended on apoptosis pathways. For compounds in sensitive cancer line, their mechanisms of mode of action were evaluated. 33-Hydroxyepigambogic acid and 35-hydroxyepigambogic acid exhibited about 1  μ M IC50 values against JAK2/JAK3 kinases and less than 1  μ M IC50 values against NCI-H1650 cell which autocrined IL-6. Thus these two compounds provided a new antitumor molecular scaffold. Our report describes 33-hydroxyepigambogic acid and 35-hydroxyepigambogic acid that inhibited NCI-H1650 cell growth by suppressing constitutive STAT3 activation via direct inhibition of JAK kinase activity.